A COMPARATIVE FEMALE CHARACTERS’ ANALYSIS IN J.R.R TOLKIEN’S LORD OF THE RINGS AND G.R.R. MARTIN’S A SONG OF ICE AND FIRE THROUGH A FOUCAULDIAN LENS - Cherouag, Mohamed El Hadi (My University, 2024)
The fantasy genre is well known for its imaginative richness and ingenuity, which managed to develop throughout time, evolving its tropes, techniques, and representations, making the distinction between its published works ever more apparent between early and current iterations. This paper conducts a comparative analysis of J.R.R. Tolkien’s The Lord of the Rings trilogy and George.R.R. Martin’s A Song of Ice and Fire, with a focus on female characters and their representation. The present study is situated within the theoretical framework of Michel Foucault’s theory to examine the dynamics of power. The analysis makes use of Foucault's ideas to study the characters and explain how modern writers subvert established narrative structures that are moulded by sexist stereotypes. The hypothesis put forth in this study suggests that while Tolkien's female characters negotiate patriarchal structures within the confines of traditional gender roles, Martin's women actively confront and subvert established power hierarchies, reflecting a more modern and nuanced understanding of gender politics. All the while highlighting how contemporary writers challenge the narrative structure shaped by classic tropes in order to revitalise the genre and turn it from a one-dimensional narrative to a nuanced form of storytelling.
Keywords: feminism; fantasy genre; female characters; Foucault’s theory; sexism